Mapping the sugar dependency for rational generation of a DNA-RNA hybrid-guided Cas9 endonuclease. Issue 1 (December 2017) - Rueda, Fernando; Bista, Michal; Newton, Matthew; Goeppert, Anne; Cuomo, M. Emanuela; Gordon, Euan; Kröner, Felix; Read, Jon; Wrigley, Jonathan; Rueda, David; Taylor, Benjamin
Abstract The CRISPR–Cas9 RNA-guided endonuclease system allows precise and efficient modification of complex genomes and is continuously developed to enhance specificity, alter targeting and add new functional moieties. However, one area yet to be explored is the base chemistry of the associated RNA molecules. Here we show the design and optimisation of hybrid DNA–RNA CRISPR and tracr molecules based on structure-guided approaches. Through careful mapping of the ribose requirements of Cas9, we develop hybrid versions possessing minimal RNA residues, which are sufficient to direct specific nuclease activity in vitro and in vivo with reduced off-target activity. We identify critical regions within these molecules that require ribose nucleotides and show a direct correlation between binding affinity/stability and cellular activity. This is the first demonstration of a non-RNA-guided Cas9 endonuclease and first step towards eliminating the ribose dependency of Cas9 to develop a XNA-programmable endonuclease. CRISPR-Cas9 systems are being continually improved to enhance specificity and improve functionality. Here the authors design hybrid DNA-RNA guide and tracr molecules to direct Cas9 nuclease activity with reduced off-target effects.